(untitled) (Journal of Patan Academy of Health Sciences, 2017)
Introductions: Kidney biopsy is the standard tool to diagnose glomerular disease (GD). There is lack of national registry of kidney biopsy for the type, incidence and prevalence of GD. We aim to review kidney biopsy at Patan Hospital for profile of GD in local scenario. Methods: This was a chart review of patients who underwent kidney biopsy at Patan Hospital, Nepal, from October 2013 to September 2015. We analyzed the data for indication of kidney biopsy, types of GD and complication of biopsy. Results: There were 117 patients who had kidney biopsies. Immunoglobulin A Nephropathy was seen in 42 (35.8%) and Lupus Nephritis in 38 (32.5%). Sub nephrotic range proteinuria with or without active urinary sediments was found in 75 (64%). Blood transfusion was required in 3 (2.5%) patients after biopsy. There was no surgical intervention or mortality related to biopsy. Conclusions: IgA Nephropathy was the commonest glomerular disease. Kidney biopsy was a safe and effective procedure.